Manifestation of intra-atomic 5d6s-4f exchange coupling in photoexcited gadolinium. (17th November 2017) - Zhang, G P; Jenkins, T; Bennett, M; Bai, Y H
Abstract: Intra-atomic exchange couplings (IECs) between 5 d 6 s and 4 f electrons are ubiquitous in rare-earth metals and play a critical role in spin dynamics. However, detecting them in real time domain has been difficult. Here we show the direct evidence of IEC between 5 d 6 s and 4 f electrons in gadolinium. Upon femtosecond laser excitation, 5 d 6 s electrons are directly excited; their majority bands shift toward the Fermi level while their minority bands do the opposite. For the first time, our first-principles minority shift now agrees with the experiment quantitatively. Excited 5 d 6 s electrons lower the exchange potential barrier for 4 f electrons, so the 4 f states are also shifted in energy, a prediction that can be tested experimentally. Although a significant number of 5 d 6 s electrons, some several eV below the Fermi level, are excited out of the Fermi sea, there is no change in the 4 f states, a clear manifestation of intra-atomic exchange coupling.